Building, coding and programming 3D models via a visual programming environment - Pinto-Llorente, Ana Mª; Casillas-Martín, Sonia; Cabezas-González, Marcos; García-Peñalvo, Francisco José (Quality & quantity, 2018)
This paper presents the findings of a study conducted in the state-funded Infant, Primary and Secondary School Santísima Trinidad in Salamanca. The main objectives of the research were, to evaluate the use of the visual programming environment, Lego Education WeDo, in natural science and to know the benefits of the use of this tool to teach abstract concepts, solve problems and motivate students. In order to achieve these objectives, we used the case study method since we focused on individuals who represented the phenomenon of our interest, and explored and investigated in depth the phenomenon in its natural context bounded by time and space. In the research were involved a teacher and fifty-two students of 4th grade of primary education. The study found that the project developed was effective to help students to achieve the learning objectives of the unit, and also to begin building, coding and programming 3D models. The research showed the teacher’ fundamental role as a guide and students’ active role as builders, programmers, or presenters. There were evidences of the possibilities offered to acquire the skills of critical thinking, creative thinking, problem solving, reflection, collaboration, communication, and time management. Due to the positive results obtained in this study, it is recommended to incorporate computational thinking in primary education and in core content areas since it is fundamental in the current society.